Controle fuzzy de um motor dc utilizando sistema de aquisição de dados e o matlab - Correia, Cainã Sagaz [UNESP] (2015)
The present work develops a fuzzy inference system to control the rotation speed of a DC motor available in Degem Kit. Therefore, it should use the fuzzy toolbox of Matlab in conjunction with the data acquisition board NI - USB - 6009, a National Instrument’s board. An introduction to fuzzy logic, the mathematical model of a DC motor and the operation of data acquisition board is presented first. Followed by the controller fuzzy model implemented using Simulink which is described in detail. Finally, the prototype is shown and the simulator results are presented